The Effects of PGR Soaking Treatment and Cow Manure Fertilizer Dosage On Corn (Zea mays L.) Variety Arjuna Growth and Yield - A Miftakhurrohmat; Fitri Yantika Nur Jannah (Nabatia, 2018)
The main objective of this investigation was to study The Effects of PGR Soaking Treatment and Cow Manure Fertilizer Dosage On Corn (Zea mays L.) Variety Arjuna Growth and Yield, this experiment was conducted at Jiken village, Tulangan, Sidoarjoduring April to July 2018,This research used a two factor Randomized Complete Block Design (RCBD) and repeated three times. The first faktor was PGR Soaking treatment (0, 15, and 20ml/liter). The second factor was Cow Manure Fertilizer (10, 20, dan 30 ton/ha). Parameters research focused on buds appeared time, plant height, the number of leaves, stem diameters, cob of corn fresh weight, cob of corn dry weight, and corn seed dry weight. This research reflectedsignificant differences interaction between PGR Soaking Treatment and Cow Manure Fertilizer Dosage in plant height (42 DAP). PGR Soaking Treatment reflected significant differences in cob of corn, number of leaves (56 DAP), and very significant differences of corn fresh weight and dry weight, and corn seed dry weight. Cow Manure Fertilizer Dosage reflected significant differences in cob of corn fresh weight and dry weight, and corn seed dry weight.